Teachers' Efforts In Creating Effective Face-To-Face Learning Communications During The PPKM Era - Vira Octavia; Sri Narti; Indria Indria (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
The purpose of this research is to find out the teachers’ efforts in creating effective learning communication by face to face during PPKM era. During Covid-19 pandemic, it is allowed to hold outdoor activities in PPKM era with health protocol. But until now, since 19 October 2021 until 8 November 2021, Bengkulu City in Bengkulu Province was in Level 2 PPKM. Make any rules are allowed to be executed especially learning and teaching process. The research method is descriptive qualitative by using effective communication theory according to effective communication law by Prijosaksono Sember (2002) in Nofrion (2019:138). Stated that there are five effective communication laws which abbreviated into one word which reflect the effective communication essense, it is REACH (Respect, Empathy, Audible, Clarity, Humble). The result of the research shows that the teachers effort in creating effective communication learning with face to face in PPKM era by using several words “halo”, “anak sholeh”,”RA Bina Ilmu”,”yel-yel yukk”. It can be concluded that the teachers’ efforts at Raudhatul Athfal (RA) Bina Ilmu in creating effective communication learning has been run well.